Design and Construction of IoT-Based Smart Wardrobe with RGB Sensor and Sound Sensor - Susanto, Nugroho; Setiawan, Doni; Sulistyo, Adi; Pratama, Aziz Yulianto; Faoziah, Nina; Dalimarta, Fahmy Ferdian (Jurnal Improsci, 2025)
This research aims to design and build a smart wardrobe based on the Internet of Things (IoT) equipped with color sensors and sound sensors. This cabinet is designed to make it easier for users to organize and find the clothes they want with the help of advanced technology. The color sensor will detect the color of the garment and allow the system to suggest a combination of garments that suit the user's preferences. Meanwhile, the voice sensor allows for control of the wardrobe through voice commands, providing convenience for users to access clothes without having to open the closet door manually. This smart cabinet uses microcontroller-based hardware connected to a mobile app to manage and monitor the status of cabinets. The integrated IoT system allows the cabinet to function automatically and respond quickly to the input received from the sensors. The results of this research are expected to produce more efficient devices for organizing and searching for clothes, as well as provide a more interactive and practical user experience. In addition, by optimizing IoT technology, this research aims to introduce a more sophisticated smart home concept, with a wardrobe as one of the elements that support the ease of daily life. Keywords: Arduino, Sound sensor, Color sensor.